Outbreak of Serogroup C Meningococcal Disease Caused by a Variant of Neisseria meningitidis Serotype 2a ET-15 in a Community of Men Who Have Sex with Men - Tsang, Raymond S.W. (American Society for Microbiology, 2003)
We describe an outbreak, in a community of men who have sex with men, of serogroup C meningococcal disease caused by a genetic variant of the serotype 2a ET-15 Neisseria meningitidis characterized by a point mutation in the gene coding for the serotype 2a antigen. A microbiological characterization of the outbreak strain is presented in this report.